PERILAKU TANAH EXPANSIF TERHADAP DAYA DUKUNG - Manoppo, Fabian J. (Sam Ratulangi University, 2013)
The important things in design of structural engineering problems such as building is foundation. Some soil problems were found in design of foundation. One of the problem is foundation buried in expansive soils. Some methods were suggested to solve these problems such as soil stabilization or computed the heave of expansive soils. In order to reduce the heave caused of expansive soil, the pressure from the above soil should be increased while controlled the settlement of foundation. This analysis was computed the bearing capacity of shallow foundation cause of expansive soil and how to control the heave. The result was shown that if the pressure from the above increased then the heave will be decreased and the cohesion of soil increased the heave was decreased too.Keywords; Bearing capacity, the heave, shallow foundation, expansive soil